2010
DOI: 10.1038/mi.2009.127
|View full text |Cite
|
Sign up to set email alerts
|

Cell-secreted Gp96-Ig-peptide complexes induce lamina propria and intraepithelial CD8+ cytotoxic T lymphocytes in the intestinal mucosa

Abstract: Induction of mucosal immunity is critical for protection from enteric pathogens. Heat shock protein gp96 is one of the primary peptide and protein chaperones located in the endoplasmic reticulum. We reported previously that a cell-secreted gp96-Ig fusion protein (gp96-Ig) mediated strong systemic, antigen-specific CD8-CTL expansion in vivo. We now evaluate the mucosal immune response to stimulation by secreted gp96 using allogeneic NIH-3T3 transfected with ovalbumin (OVA) and gp96-Ig. A single intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 47 publications
6
41
0
Order By: Relevance
“…Criteria for differential expression were an absolute change of Ͼ1.4-fold and a P value of Ͻ0.05, calculated using a moderated t test (see Materials and Methods). It has previously been described that the gp96-Ig vaccine approach (delivered by the intraperitoneal route) induces a strong mucosal immune response, while systemic immune responses are not significantly upregulated (13,14). Therefore, the observed lack of gene expression in whole blood during the vaccination phase was not surprising.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Criteria for differential expression were an absolute change of Ͼ1.4-fold and a P value of Ͻ0.05, calculated using a moderated t test (see Materials and Methods). It has previously been described that the gp96-Ig vaccine approach (delivered by the intraperitoneal route) induces a strong mucosal immune response, while systemic immune responses are not significantly upregulated (13,14). Therefore, the observed lack of gene expression in whole blood during the vaccination phase was not surprising.…”
Section: Resultsmentioning
confidence: 92%
“…This heat shock protein, similar to soluble Hsfp and hsp65 (8,9), binds to and activates dendritic cells (10) and functions as a chaperone for tumor-secreted peptides. The modified form of gp96, gp96-Ig, secreted by tumors (11), results in an enhancement of tumor antigen crosspriming of CD8 cytotoxic T lymphocytes (CTLs) (12) and induces a mucosal immune response following intraperitoneal injection of transfected cells (13). When chaperoning simian immunodeficiency virus (SIV) peptides, gp96-Ig induces a strong multifunctional memory response in the rectal and vaginal mucosae of rhesus macaques (14).…”
mentioning
confidence: 99%
“…Our present study is supported by work of Podack and colleagues showing that enforced secretion of gp96 from tumor cells enhances the generation of antitumor CD8 T cell responses. In those reports, CD11c + cells were identified as the necessary APCs for the immune response (40,41). …”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, Dr. Podack and his group have developed an innovative vaccine approach based on a genetically modified form of the endoplasmic reticulum (ER) chaperone gp96, the fusion protein gp96-Ig. The gp96-Ig vaccine is composed of live, but replication incompetent cells, containing the antigens of interest and secreting gp96-Ig, which has been introduced into the cell by transfection and G418-selection [4048]. Secreted gp96-Ig chaperones peptides (gp96 pep -Ig) come into ER via the TAP transporter [49].…”
Section: Generation Of Humanized Micementioning
confidence: 99%
“…In murine studies, nonhuman primates and in cancer patients, we have shown that gp96-Ig-based vaccines generate CD8 CTL responses to gp96-Ig-chaperoned, antigenic peptides derived from SIV or HIV and to other test antigens. Immune responses ensue systemically and are especially powerful in the intestinal, rectal and vaginal mucosa [40, 47, 51]. …”
Section: Generation Of Humanized Micementioning
confidence: 99%